EXTRAMURAL STUDIES: THE MAIN PROBLEM AND ITS SOLUTION - Darya O. Perevezentceva; Nikolai F. Stas (Открытое образование (Москва))
Control has a diagnostic, educational, evaluative and pedagogic functions in academic activities, that’s why it is the imperative element of every educational technology. The main problem of extramural studies is the lack of control during the intermediate stages of the educational process. While learning the chemistry by a student of extramural studies, the organization and resource materials which are used to minimize the negative consequences of this problem were developed and realized.